Temporal Variation of Coastal Groundwater Quality in East Coast of Terengganu, Malaysia - Hairoma, Norsyuhada; Barzani Gasim, Muhammad; Ekhwan Toriman, Mohd; Juahir, Hafizan; Azid, Azman; Hatta Abd Karim, Mohammed; Khairul Amri Kamarudin, Mohd; Mokhtar, Mazlin; Elfitri, Rahmah (International Journal of Engineering and Technology, 2018)
Coastal groundwater is extremely vulnerable to saltwater contamination. This study was conducted to investigate the potential contamination of saltwater into coastal groundwater temporally. Data was obtained from PT000017 monitoring well from 2006 to 2012. Nine parameters of water quality were involved for data analyses. Two main diagrams used for data analyses are piper diagram and hydrochemical facies evolution diagram (HFE-D). All parameters were plotted to produce a piper diagram that determine the water type between different seasons. During wet season, groundwater samples are located in domain III that represent mixed Ca-Na-HCO3 water type; 2007 groundwater sample was located in domain I, represent Ca-HCO3 water type and during 2008 groundwater sample was located in domain II, represent Na-Cl water type. During dry season, groundwater samples are located in domain II that represent mixed Ca-Na-HCO3 water type meanwhile, 2009 and 2011 groundwater samples are located in domain I, represent Ca-HCO3 water type. Subsequently, HFE-D diagram was produced to determine the evolution process of salinization or freshening of coastal groundwater. In this study, all of groundwater samples were in freshening stage except during dry season 2007 groundwater sample was in the phase of saltwater intrusion.Â Â